The Effects of Experimental Sleep Extension in Middle-to-Older-Aged Healthy Sleepers - Reynolds, Alexandria M.; Seymour, Zachary R.; Iftikhar, Imran H.; Burnette, M. Michele; Vendemia, Jennifer M. C.; Youngstedt, Shawn D. (Sleep Science, 2024)
Objectives To determine the feasibility for middle-aged and older adults to extend their time in bed by 2 h per night for 3 consecutive weeks. Other aims were to examine the effects of sleep extension on mood, cognitive performance, and cardiovascular health.Methods Ten healthy middle-aged to older adults (9 women; M = 65.20 ± 4.78 years) who reported regularly sleeping 6 to 8 h per night participated in a randomized controlled cross-over study: 3 weeks of both habitual sleep and extended sleep (1-week recovery between treatments). Participants were asked to spend 2 additional hours in bed per night during sleep extension. Cognitive (e.g., errors, response time), psychological (e.g., depression, anxiety, mood), and physiological measures (e.g., inflammation, glucose, triglycerides, blood pressure) were assessed.Results Compared with habitual sleep, time in bed increased 81.63 ± 33.11 min and total sleep time increased 66.33 ± 28.64 min during sleep extension; these variables did not significantly change during baseline or the habitual sleep treatment. No significant treatment differences were found in the cognitive, psychological, or physiological measures.Discussion Neither significant positive nor negative effects of sleep extension were found for any of the variables. In terms of feasibility, it was difficult for the participants to extend their time in bed and, subsequently, attain more sleep by the targeted amount. Sleep extension by a greater degree or longer period of times might be more likely to elicit positive or negative effects.
Keywords: inflammation; cognition; healthy volunteers; middle-aged; sleep